2019
DOI: 10.1097/md.0000000000017159
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic endovascular aortic repair in penetrating aortic ulcer combined with isolated left vertebral artery

Abstract: Rationale:Penetrating aorta ulcer (PAU) with isolated left vertebral artery (ILVA) is a rare condition, accounting for no more than 1% of all kinds of aorta diseases. And traditional treatment was open surgery with total arch replacement by elephant trunk. Here, we report a case of PAU combined with ILVA managed by thoracic endovascular aortic repair (TEVAR) technique.Patient concerns:A 65-year-old male with chronic hypertension and Nicotine abuse underwent intermittent back pain for 2 years and aggravated a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A previous study reported successful treatment of penetrating aorta ulcer with an isolated left vertebral artery through in situ fenestration and chimney technique for revascularization of isolated left vertebral artery and the LSA. [ 14 ] In order to obtain sufficient anchoring area, we created a scallop at the beginning of the coated stent to extend it to the middle of the left common carotid artery. Additionally, we used the in situ fenestration technique to reconstruct the LSA and transposed the left vertebral artery to the left carotid artery to avoid stent coverage in this patient with AD.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported successful treatment of penetrating aorta ulcer with an isolated left vertebral artery through in situ fenestration and chimney technique for revascularization of isolated left vertebral artery and the LSA. [ 14 ] In order to obtain sufficient anchoring area, we created a scallop at the beginning of the coated stent to extend it to the middle of the left common carotid artery. Additionally, we used the in situ fenestration technique to reconstruct the LSA and transposed the left vertebral artery to the left carotid artery to avoid stent coverage in this patient with AD.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of an ILVA has significant impact on the choice of aortic arch reconstruction techniques and cerebral protection methods ( 18 ). Current literature reported several options such as total open surgery ( 18 ), hybrid procedure ( 9 , 19 ) and parallel stents technique ( 20 ) to deal with aortic arch lesions and ILVAs. However, there was no consensus on the indication and strategy for ILVA reconstruction to date, as the relevant studies were scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel grafts such as the chimney technique has been used for preservation of ILVA, implying a feasible alternative with encouraging short-term results ( 20 ). However, the risk of type Ia endoleaks through the gutters and uncertainty regarding the long-term patency of artery remain a concern ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed previous cases with one or more anomalies (Table 1). 2,720 Nonami et al. 7 reported that a patient with ARSA and ILVA with aortic aneurysm successfully underwent aortic arch replacement with five branches, in 1998.…”
Section: Discussionmentioning
confidence: 99%
“…However, traditional TEVAR is unsuitable for all patients because of landing zone limitations. Other surgeons have reported aortic dissection or aneurysm with ARSA or ILVA occurring alone, treated with total endovascular repair, 912 hybrid procedure, 1217 or open surgery. 1820…”
Section: Discussionmentioning
confidence: 99%